2020
DOI: 10.1111/ene.14593
|View full text |Cite
|
Sign up to set email alerts
|

Baseline white matter hyperintensities affect the course of cognitive function after small vessel disease‐related stroke: a prospective observational study

Abstract: Background and purposeCognitive impairment is a common sequel of recent small subcortical infarction (RSSI) and might be negatively affected by preexisting cerebral small vessel disease (SVD). We investigated whether the course of cognitive function in patients with RSSI is influenced by the severity of white matter hyperintensities (WMH), an important imaging feature of SVD.MethodsPatients with magnetic resonance imaging (MRI)‐proven single RSSI were tested neuropsychologically concerning global cognition, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Finally, it is vital to take into consideration a study by Fruhwirth and colleagues [ 50 ], who investigated whether the course of cognitive function in patients with recent small subcortical infarction was influenced by the severity of WMHs. Patients were assessed neuropsychologically using tests of global cognition, processing speed, attention, and set-shifting.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is vital to take into consideration a study by Fruhwirth and colleagues [ 50 ], who investigated whether the course of cognitive function in patients with recent small subcortical infarction was influenced by the severity of WMHs. Patients were assessed neuropsychologically using tests of global cognition, processing speed, attention, and set-shifting.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fruthwirth et al found that deep WMH volume at baseline predicted recovery of set-shifting at 15 month follow up among patients with recent small subcortical infarcts: participants with no or mild deep WMH improved in set-shifting, while those with moderate to severe WMH showed no improvement ( 41 ). A similar pattern was seen for periventricular WMH (pWMH) at baseline and recovery of attention, although this interaction was no longer significant after controlling for age.…”
Section: Neuroimaging Modalities Used As Biomarkers For Cognitive Rec...mentioning
confidence: 99%
“…Nine studies (N=1873) reported presence, number, location, and size of lacunes (Supplement 9 and Figure 2). 18,21,23,26,30,31,36,41,42 Data from three studies were suitable for meta-analysis. There was no association between presence of lacunes and PSCI (3 studies, N=641, OR u =1.46, 95%CI=0.96-2.23, I 2 =0%, P=0.08) 18,30,31 .…”
Section: Lacunesmentioning
confidence: 99%